Optimalisasi Penerimaan Pajak dari Sektor UMKM di Tengah Kebijakan Insentif Pajak Pemerintah - Siti Rifqa Raihani; Irwan Triadi (AHKAM, 2026)
Although MSMEs are a fundamental pillar in the national economic structure and play an important role in maintaining Indonesia’s economic resilience against global market shocks, studies that specifically discuss the synchronization of MSME tax regulations from the perspective of fiscal justice remain limited. This study aims to analyze the synchronization of MSME tax regulations based on written legal norms and fiscal justice theory. This study employed a normative juridical method with a statutory approach and a conceptual approach. The results show that the establishment of the Kementerian UMKM through Peraturan Presiden Nomor 196 Tahun 2024 and the plan to separate the tax regime in the revision of Peraturan Pemerintah Nomor 55 Tahun 2022 constitute strategic government measures to strengthen the focus of authority and budgetary independence in empowering the micro sector. The policy is designed to create a balance between providing competitive tax incentives for PT Perorangan and individual taxpayers and maintaining the stability of state revenue through more accountable business formalization. These findings contribute to the development of studies in economic and tax law, particularly regarding the design of more adaptive fiscal policies for MSMEs. This study underscores the importance of synchronizing tax regulations that are able to support MSME empowerment while at the same time sustainably safeguarding the state’s fiscal interests.